Should Patients with Down Syndrome be Screened for Testicular Microlithiasis? - Cebeci, Ayse Nurcan; Aslanger, Ayca; Ozdemir, Mustafa (European Journal of Pediatric Surgery, 2015)
Background Testicular microlithiasis (TM) is a rare condition characterized by asymptomatic calcification of seminiferous tubules and is considered as a precursor of testicular germ cell tumors. The prevalence of TM has been reported higher in patients with Down syndrome (DS) than general population. Our aim was to determine the prevalence of TM in our patients with DS.Patients and Methods Male patients with DS confirmed by chromosomal analysis were prospectively evaluated using high resonance ultrasound. For every patient with DS, an age-matched healthy non-DS volunteer was recruited and the results were compared.Results A total of 50 testes from 25 patients between the age of newborn and 19.3 years were studied. While nine patients with DS (36%) had TM, none of controls had TM. Mean testicular volumes (TVs) of patients with DS did not differ significantly from the control group. In DS group, patients with TM were significantly older than patients without TM (mean age was 8.44 years [range, 2.0–19.3 years] and 2.39 years [range, 0.1–12.1 years], respectively, p = 0.002). TM was found positively correlated with age (r = 0.568, p = 0.003). Cryptorchidism was found in five patients in DS group (three unilateral and two bilateral) and in two controls (one unilateral and one bilateral). Of the nine patients with TM, only one patient had cryptorchidism; thus, TM was not found to be related with cryptorchidism. All the nine patients with DS and TM had normal serum levels of α-fetoprotein and β-human chorionic gonadotropin.Conclusion On the basis of the high prevalence found in our study, we suggest that all male patients with DS should be screened for TM in childhood.
Keywords: down syndrome; testicular microlithiasis; ultrasonography; testicular tumor